Cytotoxic, Cellular Antioxidant, and Antiglucuronidase Properties of the Ethanol Leaf Extract from Bulbine asphodeloides - Wilfred Otang-Mbeng; Idowu Jonas Sagbo (The Scientific World Journal)
Bulbine asphodeloides (L.) Spreng (Xanthorrhoeaceae family), popularly known in South Africa as “ibhucu” or “Balsamkopieva,” is a perennial plant traditionally used to treat skin diseases, including sunburns, rough skin, dressing burns, itches, and aging. The present study reports the cytotoxic, cellular antioxidant, and antiglucuronidase properties of the ethanol leaf extract from B. asphodeloides. The cytotoxic effect of the plant extract on human dermal fibroblast (MRHF) cells was evaluated by the bis-Benzamide H 33342 trihydrochloride/propidium iodide (Hoechst 33342/PI) dual-staining method. A validated biological cell-based assay was used to determine the cellular antioxidant activity of the extract. The antiglucuronidase and metal chelating activities were evaluated using standard in vitro methods. Lipopolysaccharide- (LPS-) induced RAW 264.7 cell model was used to determine the anti-inflammatory effect of the plant extract, and the immune-modulatory activity was performed using RAW 264.7 cells. The extract demonstrated no cytotoxic effect towards the MRHF cells at all the tested concentrations. Furthermore, the extract also possessed significant cellular antioxidant and antiglucuronidase activities, but a weak effect of metal chelating activity in a dose-dependent manner. However, the extract showed no significant anti-inflammatory and immune-stimulatory activities. Overall, the results showed that B. asphodeloides may be a useful therapeutic agent for the treatment of skin diseases, therefore supporting its ethnomedicinal usage.